2020
DOI: 10.30849/ripijp.v54i1.1298
|View full text |Cite
|
Sign up to set email alerts
|

Sintomatología asociada a trastornos de Salud Mental en trabajadores sanitarios en Paraguay: efecto COVID-19

Abstract: La enfermedad por COVID-19 no solo ha provocado un colapso del sistema sanitario y la muerte de miles de personas, sino que está repercutiendo en la salud de las personas que están brindando atención a los infectados.  En este marco, el objetivo de esta investigación fue determinar prevalencias de depresión, ansiedad, insomnio, distrés y fatiga por compasión, así como factores relacionados a la presencia de sintomatología asociada a estos trastornos en profesionales de los equipos de salud. Para esto, se encue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
26

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 21 publications
4
31
0
26
Order By: Relevance
“…A total of 36 unique samples from 33 studies (Badellino et al, 2020;Campos et al, 2020;Cénat et al, 2021;Chen et al, 2020a;Chen et al, 2020b;Civantos et al, 2020;Cortés-Álvarez et al, 2020;Dal'Bosco et al, 2020;De Boni et al, 2020;Fernández et al, 2020;Feter et al, 2021;Giardino et al, 2020;Goularte et al, 2021;Guiroy et al, 2020;Loret de Mola et al, in press;Malgor et al, 2020;Martinez et al, 2020;Medeiros et al, 2020;Monterrosa-Castro et al, 2020;Mora-Magaña et al, 2020;Paz et al, 2020;Puccinelli et al, 2021;Robles et al, 2020;Samaniego et al, 2020;Schuch et al, 2020;Scotta et al, 2021;Serafim et al, 2021;Torrente et al, 2021;Werneck et al, 2021;Jaime A. Yáñez et al, 2020; Jaime Stephen X Zhang et al, 2021;Stephen Xu Zhang et al, 2021) involving 101,772 participants from Latin America were included in this meta-analysis (Table 1). Some studies include multiple independent samples.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 36 unique samples from 33 studies (Badellino et al, 2020;Campos et al, 2020;Cénat et al, 2021;Chen et al, 2020a;Chen et al, 2020b;Civantos et al, 2020;Cortés-Álvarez et al, 2020;Dal'Bosco et al, 2020;De Boni et al, 2020;Fernández et al, 2020;Feter et al, 2021;Giardino et al, 2020;Goularte et al, 2021;Guiroy et al, 2020;Loret de Mola et al, in press;Malgor et al, 2020;Martinez et al, 2020;Medeiros et al, 2020;Monterrosa-Castro et al, 2020;Mora-Magaña et al, 2020;Paz et al, 2020;Puccinelli et al, 2021;Robles et al, 2020;Samaniego et al, 2020;Schuch et al, 2020;Scotta et al, 2021;Serafim et al, 2021;Torrente et al, 2021;Werneck et al, 2021;Jaime A. Yáñez et al, 2020; Jaime Stephen X Zhang et al, 2021;Stephen Xu Zhang et al, 2021) involving 101,772 participants from Latin America were included in this meta-analysis (Table 1). Some studies include multiple independent samples.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the random-effects model, the pooled prevalence of anxiety was 32% (95% CI: 27%-38%, I 2 = 99.8%) in the 29 studies (Figure 2A). A total of 27 samples from 24 studies (Badellino et al, 2020;Campos et al, 2020;Civantos et al, 2020;Cortés-Álvarez et al, 2020;Dal'Bosco et al, 2020;De Boni et al, 2020;Fernández et al, 2020;Feter et al, 2021;Giardino et al, 2020;Goularte et al, 2021;Guiroy et al, 2020;Loret de Mola et al, in press;Martinez et al, 2020;Medeiros et al, 2020;Mora-Magaña et al, 2020;Paz et al, 2020;Puccinelli et al, 2021;Robles et al, 2020;Samaniego et al, 2020;Schuch et al, 2020;Serafim et al, 2021;Torrente et al, 2021; Stephen X Zhang et al, in press) reported the prevalence of depression among 53,622 respondents. Among all the depression survey tools, the Patient Health Questionnaire (PHQ)-9 was the most frequently used (45.83%), followed by HADS (16.67%), DASS-21 (12.5%), and Beck Depression Inventory (BDI) (4.17%).…”
Section: Estimates Of Pooled Prevalence Of Psychological Morbidity Symptomsmentioning
confidence: 99%
“…Entre las escalas más utilizadas en dichos contextos se encuentran el "Impact of Event Scale Revised (IES-R)" (El-Zoghby et al, 2020;González-Ramírez et al, 2020;Hao et al, 2020;Parrado-González & León-Jariego, 2020;Samaniego et al, 2020;Tan et al, 2020;Varshney et al, 2020;Wang et al, 2020) y el "Post-traumatic Stress Disorder Checklist-Reduced version (PCL-C-2)" para evaluar PTSD (González-Sanguino et al, 2020); y el "Kessler Psychological Distress Vol. 13, 2021 / Special Issue: COVID-19 / ISSN 2007 -0705…”
Section: Introductionunclassified
“…Hasta el momento, entre los instrumentos más utilizados en investigaciones sobre el impacto psicológico de la COVID-19, se ubican las escalas para evaluar sintomatología ansiosa, como el "Generalized Anxiety Disorder Scale" (GAD en sus diferentes versiones) (González-Sanguino et al, 2020;Samaniego et al, 2020), sintomatología depresiva con el "Patient Health Questionnaire (PHQ 9 o 2)" (González-Sanguino et al, 2020;Samaniego et al, 2020); o ambas, con la escala "Depression, Anxiety and Stress Scales (DASS-21)" (Hao et al, 2020;Orellana & Orellana, 2020;Tan et al, 2020;Wang et al, 2020). En otras investigaciones se ha empleado el "Cuestionario General de Salud de Goldberg (GHQ-12)", con la intención de evaluar de forma más integral el bienestar general y la presencia de ciertos estados emocionales asociados a malestares psicológicos debido a la pandemia (Parrado-González & León-Jariego, 2020).…”
Section: Introductionunclassified
“…Strategic alliances during the pandemic will lead to effective contextual intervention. As the odds of significant consequences in mental health are high [13,56], guidelines from the Inter-American Psychological Society state that "the presence of psychologists in the mass media is crucial to carry a message of calm to the population" [19]. Moreover, Zaka et al [69] highlighted the urgent need to implement mental health interventions to front-line medical staff working with Covid-19.…”
Section: Introductionmentioning
confidence: 99%